Volumizing Threads (Jamber) in the Midface and Managing Side Effects: Clinical Cases - Yi, Kyu-Ho; Park, Soo-Yeon (Archives of Plastic Surgery, 2024)
The clinical application of polydioxanone (PDO) threads, traditionally utilized for tissue lifting, is now being explored for its volumizing effects in midface rejuvenation. The novel approach involves employing PDO volumizing threads to achieve physical augmentation akin to a “solid filler.” The study introduces a more convenient insertion method for these threads, prioritizing ease and efficacy. Clinical cases demonstrate the efficacy of volumizing threads in addressing midface concerns, such as nasolabial folds and midcheek grooves. Additionally, the integration of volumizing threads to provide support in sagging areas is examined for achieving natural-looking enhancements. While highlighting positive outcomes, potential side effects like thread protrusion are addressed, along with strategies for their mitigation. Volumizing threads are presented as a suitable procedure for patients wary of traditional fillers or seeking subtle enhancements, with the recommendation of combining them with cog threads for those desiring more pronounced changes in facial contour. In summary, volumizing thread offers a minimally invasive alternative with fewer side effects for midface rejuvenation.
Keywords: jamber thread; volumizing thread; midface rejuvenation; thread lifting